KELAYAKAN BUKU POP UP RANGKAIAN SERI KEGIATAN SISWA TERINTEGRASI PENDEKATAN SAINTIFIK - Dyoty Auliya Vilda Ghasya; Gio Mohamad Johan; Lili Kasmini; Pupun Nuryani; Waspodo Tjipto Subroto (Jurnal Tunas Bangsa, 2019)
This study aims to determine the feasibility of language, presentation and graphical results of the development of pop-up books series of student activities integrated scientific approach to improve environmental problem solving skills for elementary school students in the framework of the 2013 curriculum. This type of research is research and development or R & D (Research and Development) a type of 4-D model that produces a product in the form of a pop up book series of student activities integrated scientific approach. At this stage will review the aspects of language feasibility, presentation and graphics of the development of pop-up books series of student activities integrated scientific approach. Data collection techniques to determine aspects of language feasibility, presentation and graphics of pop-up books series of student activities integrated scientific approach is a check list technique . The instrument used is a check list instrument validating language feasibility, presentation and graphics. Data analysis techniques as a result of filling in the check list instrument validation of language feasibility, presentation and graphics by experts, will be analyzed quantitatively descriptively. The results of the validation of language feasibility, recitation and grammar of pop up books in a series of student activities integrated with the scientific approach are feasible to be applied in learning in elementary schools. Abstrak Penelitian ini bertujuan untuk mengetahui kelayakan bahasa, penyajian dan kegrafikan hasil pengembangan buku pop up rangkaian seri kegiatan siswa terintegrasi pendekatan saintifik untuk meningkatkan keterampilan menyelesaikan masalah lingkungan sekitar bagi siswa Sekolah Dasar dalam kerangka Kurikulum 2013. Jenis penelitian ini merupakan penelitian dan pengembangan atau R&D (Research and Development) jenis 4-D model yang menghasilkan produk berupa buku pop up rangkaian seri kegiatan siswa terintegrasi pendekatan saintifik. Pada tahapan ini akan mengulas aspek kelayakan bahasa, penyajian dan kegrafikan pengembangan buku pop up rangkaian seri kegiatan siswa terintegrasi pendekatan saintifik Teknik pengambilan data untuk mengetahui aspek kelayakan bahasa, penyajian dan kegrafikan pengembangan buku pop up rangkaian seri kegiatan siswa terintegrasi pendekatan saintifik adalah teknik check list. Adapun instrumen yang digunakan adalah instrumen check list validasi kelayakan bahasa, penyajian dan kegrafikan. Teknik analisis data hasil pengisian instrumen check list validasi kelayakan bahasa, penyajian dan kegrafikan oleh ahli, akan dianalisis secara deskriptif kuantitatif. Hasil validasi kelayakan bahasa, pengajian dan kegrafikan buku pop up rangkaian seri kegiatan siswa terintegrasi pendekatan saintifik adalah layak diterapkan dalam pembelajaran di sekolah dasar. Kata Kunci: Kelayakan Buku Pop Up